The Effect of Spectator-Based Brand Equity on Behavioral Intentions in Football Club - Muhammad Naufal Makarim (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2018)
Purpose – The purpose of this paper is to find out the effect of Spectator-Based Brand Equity on Behavioral Intentions in Football Club. Design/methodology/approach – The research is descriptive in nature that used survey data in the form of questionnaire from 100 respondent from each sample. Findings – The model developed in this study identifies that social interaction, team success, and internalization were the significant positive predictors of behavioral intentions among the overall sample. These findings highlight the importance of studying different types of consumers and suggest managerial implications, such as the need for clubs to establish reciprocal relationships with fans in order to increase their levels of internalization and contribute to increased behavioral intentions. Research limitations/implications – This research only focuses on perception from Indonesian football fans towards major European football club and might not be representative of other football leagues in Europe and around the world.  Originality/Value – This research offers a framework that can help football club managers plan marketing strategies to approach different segment of customers.